A Descriptive Study On Teaching Vocabulary To The Fifth Grade Students Of SDN 1 Pugeran, Karangdowo, Pedan, Klaten In 2012/2013 Academic Year - Rahayu., Reni Nila, Aryati Prasetyarini, S. Pd, M. Pd, Drs. Sigit Haryanto, M.Hum (2013)
This research aims at describing the teaching-learning process of vocabulary at the fifth grade of SDN 1 Pugeran, Karangdowo, Pedan, Klaten in 2012/2013 academic year, the problems faced by the teacher and the students, and the problems solved by the teacher. This research is a descriptive qualitative research. The researcher collected the data by observing the teaching learning-process of vocabulary and conducting an interview. The data are, field note and interview script. The method of collecting data are observation, interview, and document. And the techniques for analyzing data include data reduction, data display, and conclusion and verification. The result of the research shows that the first, the materials are taken from text book, namely Kreatif Berbahasa Inggris and worksheet or in Indonesian it is called Lembar Kerja Siswa (LKS) Practice Bahasa Inggris. The second, the media for teaching vocabulary are picture and real thing around the students. The third, the techniques for teaching vocabulary are drilling, repetition, memorization, discussion, and filling the blank. The fourth, the problems faced by the teacher and the students are; a. the size of the class, b. student's motivation, c. preparation, d. classroom management. And the last, the problem solving used by the teacher are should prepare interesting materials, has to be more creative and innovative, make the sequence of the material, and give some tasks to the students.